Ability of Different Measures of Adiposity to Identify High Metabolic Risk in Adolescents - Carla Moreira; Rute Santos; Susana Vale; Paula C. Santos; Sandra Abreu; Ana I. Marques; Luísa Soares-Miranda; Jorge Mota (Hindawi Limited, 2011)
Introduction. This study aimed to evaluate the screening performance of different measures of adiposity: body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) for high metabolic risk in a sample of adolescents. Methods. A cross-sectional school-based study was conducted on 517 adolescents aged 15-18, from the Azorean Islands, Portugal. We measured fasting glucose, insulin, total cholesterol (TC), HDL-cholesterol, triglycerides, and systolic blood pressure. HOMA and TC/HDL-C ratio were calculated. For each of these variables, a Z-score was computed by age and sex. A metabolic risk score (MRS) was constructed by summing the Z-scores of all individual risk factors. High risk was considered when the individual had ≥1SD of this score. Receiver-operating characteristics (ROC) were used. Results. Linear regression analyses showed that, after adjusting for age and pubertal stage, all different measures of adiposity are positively and significantly associated with MRS in both sexes, with exception of WHtR for boys. BMI, WC, and WHtR performed well in detecting high MRS, indicated by areas under the curve (AUC), with slightly greater AUC for BMI than for WC and WHtR in both sexes. Conclusion. All measures of adiposity were significantly associated with metabolic risk factors in a sample of Portuguese adolescents.